Multi-objective thermo-economic optimization of a marine tubular cooler using the tube distribution algorithm - Kaya, Ibrahim; Ust, Yasin; Ezgi, Cuneyt (SPRINGER, 2026)
The design of shell-and-tube heat exchangers often depends on iterative geometric estimation and empirical correlations, which can increase uncertainty and limit design flexibility. To address this limitation, this study develops a new Tube Distribution Algorithm (TDA) capable of determining tube bundle geometry directly from input parameters without requiring conventional tube count or shell diameter correlations. TDA is integrated with heat transfer coefficient and pressure loss models for both tube- and shell-side flows, and used with the epsilon-NTU method to enable thermal performance predictions. A seawater-cooled heat exchanger case is analyzed and validated against reference data, where geometric and thermal deviations remain below 4%, demonstrating model reliability. Following validation, a multi-objective optimization is conducted using NSGA-II algorithm to minimize annual total cost and heat exchanger volume for five TEMA shell configurations. The resulting Pareto fronts reveal a clear trade-off between economic performance and compactness. Among optimal designs, the E-type shell exhibits the lowest annual cost, the F-type shell achieves the smallest volume, while J-, G-, and H-type shells provide balanced intermediate solutions. The study highlights the functionality of TDA for tube bundle generation and offers an effective decision-making approach for selecting cost-efficient and compact heat exchanger configurations in thermal applications.
Keywords: SHELL-AND-TUBE; HEAT-EXCHANGER DESIGN; GENETIC ALGORITHMS; MASS-TRANSFER; COST; EQUATION; BAFFLES; Thermodynamics; Mechanics